2022
DOI: 10.1093/nsr/nwac079
|View full text |Cite
|
Sign up to set email alerts
|

Achieving ultrahigh electrochemical performance by surface design and nanoconfined water manipulation

Abstract: The effects of nanoconfined water and charge storage mechanism are crucial in achieving ultrahigh electrochemical performance of two-dimensional (2D) transition metal carbides (MXenes). We propose a facile method to manipulate the nanoconfined water through surface chemistry modification. By introducing oxygen and nitrogen surface groups, more active sites were created for Ti3C2 MXene, also with the interlayer spacing significantly increased by accommodating three-layer nanoconfined water. Exceptionally high c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…The crystalline phase of the CrN 4 /MXene and CrO 4 /MXene electrodes was studied with X-ray diffraction (XRD), which exhibited no evident changes after N-doping, in good agreement with a pure MXene electrode (Figure d). , However, the lattice constant of CrN 4 /MXene ( a = 3.9532) was slightly larger than that of CrO 4 /MXene ( a = 3.1061), suggesting that the N-doping led to distortion of the lattice. Likewise, Raman spectra of the CrN 4 /MXene electrode had a blue shift compared with the CrO 4 /MXene electrode, possibly due to an increase in the grain size during the N-doping (Figure e).…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…The crystalline phase of the CrN 4 /MXene and CrO 4 /MXene electrodes was studied with X-ray diffraction (XRD), which exhibited no evident changes after N-doping, in good agreement with a pure MXene electrode (Figure d). , However, the lattice constant of CrN 4 /MXene ( a = 3.9532) was slightly larger than that of CrO 4 /MXene ( a = 3.1061), suggesting that the N-doping led to distortion of the lattice. Likewise, Raman spectra of the CrN 4 /MXene electrode had a blue shift compared with the CrO 4 /MXene electrode, possibly due to an increase in the grain size during the N-doping (Figure e).…”
Section: Resultsmentioning
confidence: 62%
“…29,30 The crystalline phase of the CrN 4 /MXene and CrO 4 / MXene electrodes was studied with X-ray diffraction (XRD), which exhibited no evident changes after N-doping, in good agreement with a pure MXene electrode (Figure 2d). 31,32 However, the lattice constant of CrN 4 /MXene (a = 3.9532) due to an increase in the grain size during the N-doping (Figure 2e). In addition, the Fourier transform infrared (FTIR) spectrum of CrN 4 /MXene (Figure 2f) exhibited a decrease in the −OH intensity at 3400 cm −1 and an increase in bonds, 34,35 underscoring the successful incorporation of N elements into the MXene matrix and their coordination with Cr atoms.…”
Section: Resultsmentioning
confidence: 99%
“…The hydrophilic, N-O-terminated interlayer chemistry caused a partial interlayer hydration after soaking of the electrode in electrolyte for several hours, and an increasing number of water molecules entering the interlayer space during proton intercalation. 51,52 Similar effects of nanoconfinement chemistry design were also demonstrated for lithium intercalation from organic electrolyte by Ba ¨rmann et al, who utilized acidic or basic post-synthesis treatment of Ti 3 C 2 T x MXenes. 53 The authors found large structural changes during lithium intercalation via in situ XRD only for base-treated MXene, which was ascribed to cointercalation of carbonate solvents, which was not observed for acid-treated MXenes.…”
Section: Controlling Ion Solvation By Surface Termination Chemistrymentioning
confidence: 56%
“…The electrodes prepared by the “sacrificial cation” method have strong hydrophilicity with aqueous electrolyte, which is favorable for energy storage. 43 However, it is well known that alkylammonium cations easily decompose into NH 3 and acid during calcination (will be discussed in Fig. 3(f)).…”
Section: Resultsmentioning
confidence: 99%